Systemic lupus erythematosus in a multiethnic cohort: LUMINA XXXV. Predictive factors of high disease activity over time. Issue 9 (26th January 2006) - Alarcón, G S; Calvo-Alén, J; McGwin, G; Uribe, A G; Toloza, S M A; Roseman, J M; Fernández, M; Fessler, B J; Vilá, L M; Ahn, C; Tan, F K; Reveille, J D
Abstract : Aim: To ascertain the predictive factors of high levels of disease activity in systemic lupus erythematosus (SLE). Patients and methods: Patients with SLE (American College of Radiology criteria), aged ⩾16 years, with disease duration ⩽5 years and of Hispanic (Texas and Puerto Rico), African American and Caucasian ethnicities, were included. The outcome was high disease activity at any time (Systemic Lupus Activity Measure—Revised >10). A basic multivariable model (including age, sex, ethnicity, health insurance, social support, abnormal illness-related behaviours, helplessness and prior disease activity) was first examined. Additional models were built by including other variables. Results: 554 patients (100 Hispanics from Texas, 94 Hispanics from Puerto Rico, 199 African Americans, 161 Caucasians) and 2366 visits were analysed; 47% of the patients and 29% of the visits met the definition of high disease activity (more common among African Americans (72.0%) and Hispanics from Texas (71.3%) than among Caucasians (43.9%) and Hispanics from Puerto Rico (31.9%)). Variables found to predict high levels of disease activity were Hispanic (from Texas) and African American ethnicities, lack of health insurance, helplessness, abnormal illness-related behaviours and poor social support; age was negatively associated with high levels of disease activity. African admixture and anti-double-stranded DNA antibodies also predicted high levels of disease activity, as did prior disease activity. None of the human leucocyte antigen variables were retained in the models. Conclusions: Socioeconomic–demographic (age, ethnicity, health insurance), behavioural and psychological variables are important mediators of high levels of disease activity in SLE during its course. Interventions aimed at modifiable factors may improve the outcomes of SLE.